The plastic scintillator for n/γ-discrimination with alkyl-substituted PPO derivative. - Zhmurin, P.N.; Eliseev, D.A.; Pereymak, V.N.; Svidlo, O.V.; Gurkalenko, Yu.A. (Functional Materials, 2017)
A new polystyrene-based plastic scintillator for pulse shape n/γ-discrimination is obtained by using alkyl-substituted PPO derivative as scintillation dopant. The microhardness and FOM of the new PS is measured. The microhardness is equal to 39 MPa, and FOM on 2 MeVee level is equal 2.12. Also it is established, the new PS has high long-term stability.